Event-driven PID control of autonomous quadrotor helicopters. Issue 2 (June 2018) - Ye, Qian
This paper proposes an event-driven PID control mechanism for autonomous quadrotor helicopters that will reduce the usage of communication channels. Compared to traditional PID controller, the event-driven PID controller can maintain the satisfactory stabilization effect with the ability of reducing the number of transmissions significantly. The simplified dynamics model of quadrotor helicopter is also established. Finally, the improvements realized by the developed method are verified in the computer simulations.